Fat phenotype, associated factors and rs9939609 polymorphism of the FTO gene - William Alves Lima; Maria Fátima Glaner; Aline Pic Taylor (Universidade Federal de Santa Catarina, 2010)
The purpose of this work was to review the main results of studies that have analysed the relationship between the rs9939609 single nucleotide polymorphism (SNP) of the FTO gene and the manifestation of overweight/obesity with its associated co-morbidity, and to discuss the interaction of this polymorphism with the other factors which cause obesity. The search was performed using the MEDLINE, Highwire, Science Direct and SciELO databases, applying the following key words: FTO rs9939609, obesity genetic, gene associated obesity, FTO contributes obesity. Inclusion criteria were: original articles where the search was performed in humans and including the rs9939609. Articles that analysed the FTO gene associated with preinstalled hormonal diseases were excluded. Of the several SNP associated with the FTO gene, rs9939609 has been the most researched (studied). This SNP comprises the A and T alleles, with the A homozygote being most susceptible to the development of overweight/obesity in all age ranges, especially in the caucasian population. In this situation, the control of environmental factors (alimentation and physical activity) can prevent the excessive build up of fats. Obesity is related to the development of non-transmissible chronic illnesses. Association of rs9939609 polymorphism with the lipidic profile and glycemia were observed. The practicing of physical exercise and feeding habits seem to be the main contributors in the development of overweight/obesity and its resulting co-morbidity.